2022
DOI: 10.1017/s0033291722002173
|View full text |Cite
|
Sign up to set email alerts
|

Pre-COVID brain functional connectome features prospectively predict emergence of distress symptoms after onset of the COVID-19 pandemic

Abstract: Background Persistent psychological distress associated with the coronavirus disease 2019 (COVID-19) pandemic has been well documented. This study aimed to identify pre-COVID brain functional connectome that predicts pandemic-related distress symptoms among young adults. Methods Baseline neuroimaging studies and assessment of general distress using the Depression, Anxiety and Stress Scale were performed with 100 healthy individuals prior to wide recognition of the health risks associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Further, research has linked DMN alterations to depressive rumination (Zhou et al., 2020) and suggests its protective role in mitigating negative emotions (Akiki, Averill, & Abdallah, 2017; Chin Fatt et al., 2020; Qin et al., 2022) as well as enhancing resilience among unaffected siblings of individuals with BD (Doucet, Bassett, Yao, Glahn, & Frangou, 2017). The disruption of intrinsic coherence within the DMN may contribute to the heterogeneous forms of emotional arousal associated with risk for BD (Lindquist, Wager, Kober, Bliss‐Moreau, & Barrett, 2012; Pan et al., 2022; Suo et al., 2022), and increased connectivity in the DMN may also predict depression treatment response (Singh et al., 2021). Intriguingly, genetic variations linked to heritable forms of BD may shed light on how DMN disorganization increases vulnerability to BD development or exacerbates the progression of depression and anxiety symptoms (Buckner & DiNicola, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, research has linked DMN alterations to depressive rumination (Zhou et al., 2020) and suggests its protective role in mitigating negative emotions (Akiki, Averill, & Abdallah, 2017; Chin Fatt et al., 2020; Qin et al., 2022) as well as enhancing resilience among unaffected siblings of individuals with BD (Doucet, Bassett, Yao, Glahn, & Frangou, 2017). The disruption of intrinsic coherence within the DMN may contribute to the heterogeneous forms of emotional arousal associated with risk for BD (Lindquist, Wager, Kober, Bliss‐Moreau, & Barrett, 2012; Pan et al., 2022; Suo et al., 2022), and increased connectivity in the DMN may also predict depression treatment response (Singh et al., 2021). Intriguingly, genetic variations linked to heritable forms of BD may shed light on how DMN disorganization increases vulnerability to BD development or exacerbates the progression of depression and anxiety symptoms (Buckner & DiNicola, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We constructed the brain functional connectome using an atlas with a parcellation system in which seed regions were labeled according to a community of seven canonical brain networks (Chin Fatt et al., 2020; Pan et al., 2022; Yeo et al., 2011) that were derived from Yeo's template with 100 cortical parcels and 36 subcortical parcels of Brainnetome (for details of network distribution, see Figure S2) (Fan et al., 2016; Schaefer et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(iv) Brain features prior to the COVID-19 epidemic are useful for predicting the later emergence of distress [78]. Distress prediction was found significant by tenfold cross-validation with linear regression (brain features were employed as independent variables) [78].…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Evidence of brain plasticity related to volume change patterns has been provided in healthy adults, who were not somatically affected by COVID-19 infection following the real-life external event of the global pandemic. The high rate of psychological distress (stress and anxiety) attributed to social effects of the COVID-19-related lockdown, such as social isolation and perceived uncertainty, seemed to be associated with the transient volumetric enlargement of some brain regions (amygdala, putamen, and ventral anterior temporal cortices) [ 9 ]. In addition, a recent fMRI study [ 10 ] focused on neural correlates of psychological general distress and showed that some brain features prior to the COVID-19 epidemic could predict the later emergence of distress, mainly including within and between the default mode network (DMN) connection patterns, with the left hippocampus emerging as the most critical hub region.…”
Section: Introductionmentioning
confidence: 99%